United Arab Emirates : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues and Statistical Appendix Paper look at the global spillovers to the United Arab Emirates (UAE) financial system. It finds an uneven degree of spillovers to different segments of the UAE financial system. Regarding domestic equity markets, the combined market capitalization losses in the Abu Dhabi and Dubai stock exchanges between September 2008 and end-March 2012 exceeded USD 100 billion. The paper concludes that although financial vulnerabilities of the UAE have decreased since the 2008 global real estate collapse, given UAE's interconnectedness, it remains exposed to global financial conditions.